2020
DOI: 10.1090/bproc/51
|View full text |Cite
|
Sign up to set email alerts
|

Zeros of a one-parameter family of harmonic trinomials

Abstract: It is well known that complex harmonic polynomials of degree n may have more than n zeros. In this paper, we examine a one-parameter family of harmonic trinomials and determine how the number of zeros depends on the parameter. Our proof heavily utilizes the Argument Principle for Harmonic Functions and involves finding the winding numbers about the origin for a family of hypocycloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In [2], the authors provide a way to count the roots for the family of harmonic trinomials when a = 1, c = −1 and b ∈ (0, ∞). Moreover, the maximum number of roots for this family is n+2m, see Theorem 1.1 in [2].…”
Section: Introduction Main Results and Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [2], the authors provide a way to count the roots for the family of harmonic trinomials when a = 1, c = −1 and b ∈ (0, ∞). Moreover, the maximum number of roots for this family is n+2m, see Theorem 1.1 in [2].…”
Section: Introduction Main Results and Its Consequencesmentioning
confidence: 99%
“…In [2], the authors provide a way to count the roots for the family of harmonic trinomials when a = 1, c = −1 and b ∈ (0, ∞). Moreover, the maximum number of roots for this family is n+2m, see Theorem 1.1 in [2]. As a consequence of our main result Theorem 1.2 we obtain Corollary 1.4 which yields that any harmonic trinomial has at most n + 2m roots.…”
Section: Introduction Main Results and Its Consequencesmentioning
confidence: 99%
“…Recently, Brilleslyper et al [3] studied on the number of zeros of harmonic trinomials of the form p c (z) = z n + cz k − 1 where 1 ≤ k ≤ n − 1, n ≥ 3, c ∈ R + , and gcd(n, k) = 1. They showed that the number of zeros of p c (z) changes as c varies and proved that the distinct number of zeros of p c (z) ranges from n to n + 2k.…”
Section: Introductionmentioning
confidence: 99%
“…For an overview of the topic, see Duren [12] and Dorff and Rolf [13]. It was shown by Bshouty et al [14] that there exists a complex-valued harmonic polynomial f = h + g, such that h is an analytic polynomial of degree n, g is an analytic polynomial of degree m < n and f has exactly n 2 zeros counting with multiplicities in the field of complex numbers, C. We are motivated by the work of Brilleslyper et al [15], Kennedy [7], and Dehmer [2] on the number and location of zeros of trinomials. Recently, Brilleslyper et al [15] studied the number of zeros of harmonic trinomials of the form p c (z…”
Section: Introductionmentioning
confidence: 99%
“…Among other things, they used the argument principle for harmonic function that can be formulated as a direct generalization of the classical result for analytic functions (Duren et al [16]). An interesting open problem raised in [15] was finding where the zeros of this trinomials are located and deciding whether the value of c affects the zero inclusion regions of p c (z).…”
Section: Introductionmentioning
confidence: 99%